Inaugural NxGV Challenge 2025 winners announced - Siti Nur Azwin, Zulkapri (MotaAuto.com, 2025)
The winning teams of the inaugural NxGV Challenge 2025, co-organised by MARii (Malaysia Automotive Robotics & IoT Institute) and SAE Malaysia, and supported by Perodua, were announced today at a prize-giving ceremony held at the Malaysia Auto Show 2025.